The 10 Golden Rules of Customer Service - Duncan, Deb; Duncan, Todd (Ascent Audio, 2019)
Through the story of a $6,000 Egg, Deb and Todd Duncan reveal that even the smallest interactions have the power to create lifelong patrons or alienate once-devoted customers. The 10 Golden Rules of Customer Service represents the costly mistake of removing customer satisfaction from the bottom line. The teachable moments divulged throughout the audiobook transcend industry or career level and encourages everyone to contribute. You must go above and beyond in order to get ahead.